2019
DOI: 10.1074/jbc.ra118.006314
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the integrin Mac-1 and signal regulatory protein α (SIRPα) mediates fusion in heterologous cells

Abstract: Macrophage fusion leading to the formation of multinucleated giant cells is a hallmark of chronic inflammation. Several membrane proteins have been implicated in mediating cell-cell attachment during fusion, but their binding partners remain unknown. Recently, we demonstrated that interleukin-4 (IL-4)induced fusion of mouse macrophages depends on the integrin macrophage antigen 1 (Mac-1). Surprisingly, the genetic deficiency of intercellular adhesion molecule 1 (ICAM-1), an established ligand of Mac-1, did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…SIRPα (MFR), another member of the Ig superfamily, is involved in macrophage fusion, which accompanies chronic inflammatory conditions. The α M I domain mediates the interaction of CR3 with this counterreceptor ( 210 ) and exhibits binding to the soluble Ig1-2-3 ectodomains of SIRPα ( 199 ). Interestingly, the inactive form of α M I can still bind SIRPα, albeit to a lesser extent ( 199 ).…”
Section: Cr3 Modulating Leukocyte Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRPα (MFR), another member of the Ig superfamily, is involved in macrophage fusion, which accompanies chronic inflammatory conditions. The α M I domain mediates the interaction of CR3 with this counterreceptor ( 210 ) and exhibits binding to the soluble Ig1-2-3 ectodomains of SIRPα ( 199 ). Interestingly, the inactive form of α M I can still bind SIRPα, albeit to a lesser extent ( 199 ).…”
Section: Cr3 Modulating Leukocyte Functionmentioning
confidence: 99%
“…The α M I domain mediates the interaction of CR3 with this counterreceptor ( 210 ) and exhibits binding to the soluble Ig1-2-3 ectodomains of SIRPα ( 199 ). Interestingly, the inactive form of α M I can still bind SIRPα, albeit to a lesser extent ( 199 ). Basic amino acids flanked by lipophilic residues were identified as binding motifs within SIRPα ( 49 ).…”
Section: Cr3 Modulating Leukocyte Functionmentioning
confidence: 99%
“…Therefore, other unknown factors seem to be involved in MFR-mediated osteoclast multinucleation. Podolnikova et al recently reported that integrin macrophage antigen 1 (Mac-1) expressed on macrophages is a counter-receptor for MFR, and that their interaction is involved in macrophage fusion [ 104 ].…”
Section: Cd47-mfrmentioning
confidence: 99%
“…Macrophages spontaneously fuse with colon carcinoma and melanoma cell lines [ 67 ]. The idea of heterotypic macrophage fusion is supported by the fact that αMβ2 integrin-overexpressed HEK293 cells are able to fuse with the signal regulatory protein α (SIRPα)-overexpressed HEK293 cells in the presence of IL-4 [ 68 ]. Cell fusion does not occur among HEK293 cells, and those overexpressed either αMβ2 integrin or SIRPα alone.…”
Section: Mode Of Phagocyte Fusionmentioning
confidence: 99%
“…Migrating cells should recognize other cells and check fusion competency to avoid aberrant fusion. Many molecules are expected to be involved in the recognition process [ 12 ], including CD9 [ 129 ], CD200 [ 130 ], Connexin 43 [ 131 ], E-cadherin [ 132 ], protocadherin-7 [ 133 ], phosphatidylserine [ 134 ], and Mac-1/SIRPα [ 68 ].…”
Section: Multiple Roles Of the Actin Cytoskeleton In Phagocyte Mulmentioning
confidence: 99%